Impact of the geriatric assessment on cancer-directed systemic therapy in older Indian persons with cancer: An observational study - Vanita Noronha; Abhijith Rao; Shreya Gattani; Anant Ramaswamy; Anita Kumar; Sharath Kumar; Renita Castelino; Ratan Dhekale; Jyoti Krishnamurthy; Akash Pawar; Sarika Mahajan; Anuradha Daptardar; et al. (Cancer Research, Statistics, and Treatment, 2022)
Background: The geriatric assessment is a multidimensional evaluation of an older person. Globally, it is reported that geriatric assessments can lead to a change in the oncologic therapy decisions in approximately 28% of patients, but there are no Indian data regarding this. Objectives: We aimed to assess the proportion of patients in whom there was a change in the planned cancer-directed therapy following evaluation in the geriatric oncology clinic. Furthermore, we studied the proportion of patients who were recommended interventions for non-oncologic vulnerabilities and the factors associated with the change in the cancer-directed treatment plan following the geriatric assessment. Materials and Methods: This was an observational study conducted in the Department of Medical Oncology at the Tata Memorial Hospital, Mumbai, India. Patients aged 60 years and over with a diagnosis of malignancy were evaluated in the geriatric oncology clinic. The results of the geriatric assessment were entered in the electronic medical records (EMR). The systemic therapy plan before the geriatric assessment and the final therapy plan were retrospectively captured from the EMR. Any change in the systemic therapy plan following the geriatric assessment was recorded. Results: We enrolled 617 patients in the study between June 2018 and September 2021. The median age was 69 years (range, 60–100); 470 (76.2%) were men. The common malignancies were lung cancer in 243 (39.4%) and gastrointestinal in 208 (33.7%). The intent of therapy was palliative in 339 (54.9%) patients. There were 498 (80.7%) patients who were vulnerable or frail on the geriatric assessment. Following their geriatric assessment, systemic therapy plans were changed in 239 (38.7%) patients. The most common treatment change was deintensification in 198 patients (32.1%), comprising dose reduction in 83 (13.4%), a decrease in the number of chemotherapy medicines in 23 (3.7%), the substitution of chemotherapy by targeted therapy (4, 0.6%), oral hormonal therapy (4, 0.6%), oral tyrosine kinase inhibitor (16, 2.6%), immunotherapy (7, 1.1%), and withholding systemic therapy in 55 (8.9%) patients. Withholding systemic therapy included a change from chemoradiotherapy to radical radiation alone in 26 (4.2%), withholding neoadjuvant or adjuvant chemotherapy in 8 (1.3%), and a change to best supportive care in 21 (3.4%). Conclusions: The results of the geriatric assessment led to a change in the systemic therapy plan in almost 40% of older Indian patients with cancer. The geriatric assessment adds valuable information to the oncologic decision-making process for older persons with cancer. (Clinical Trials Registry-India: CTRI/2020/04/024675).